(untitled) (Journal of Experimental and Clinical Anatomy, 2014)
Introduction: Gastrointestinal ulcers and stomach bleeding are amongst the main undesirable side effects of aspirin taken by mouth. The present study examined the histological and histomorphometric changes in the stomach and duodenum, following oral administration of aspirin to Wistar rats, as well as the effects on body weight and packed cell volume (PCV). Materials and Methods: Twenty adult Wistar rats weighing between 160 and 210 g were randomly divided into four groups of five rats each. Group A served as control, while Group B and C received the dose equivalent of 150 mg/day and 300 mg/day in a 70 kg human respectively for 2 weeks. Results: The study showed a dose dependent significant reduction (P < 0.001) in weight of aspirin treated rats and significantly reduced (P < 0.001) PCV in treated rats. Histological findings in treated rats showed erosion of the epithelial lining and mucosa layer of stomach and duodenum. Histomorphometric measurements showed a significant decrease (P < 0.05) in thickness of the mucosa layers of the stomach and duodenum, as well as significant decrease (P < 0.05) in glandular layer and villi height following aspirin treatment. Conclusion: The present suggest that by causing gastrointestinal bleeding and ulcerative changes, oral administration of aspirin reduces the mucosa surface area of stomach and duodenum.